(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background The risk of occupationally related lung cancer, as well as pleural mesothelioma, in association with genetic polymorphisms, has been investigated with contradictory results. This systematic review aims to summarize the current knowledge on the relationship between genetic polymorphisms, occupational exposures, and lung cancer and pleural mesothelioma. Methods We searched MEDLINE, ISI Web of science, and SCOPUS online databases for all articles published in English language up to September 2016. Studies were considered eligible if they had assessed the association between occupational exposures and lung cancer/pleural mesothelioma in relation to genetic polymorphisms. Results Sixteen studies were included, of which eleven on lung cancer and six on mesothelioma, of which one was in common. NAT2 slow acetylator genotype confers an increased risk of pleural mesothelioma in subjects exposed to asbestos (OR=2.10; 95% CI=1.10-4.10), especially in combination with the GSTM1 null genotype (OR=3.60; 95% CI=1.30-9.60). GSTT1 null and CYP1A1 Msp1 T6235C (T/C+C/C) genotype carriers exposed to arsenic, uranium, asbestos and other chemical agents have an increased risk of lung cancer respect to not exposed wild type genotypes (OR=1.33; 95% CI=0.67-2.64, OR=2.20; 95% CI=1.11-4.35, respectively). Conclusion Genetic polymorphisms might modulate individual susceptibility to lung cancer and pleural mesothelioma in occupationally exposed subjects.